2014
DOI: 10.1080/09602011.2014.913530
|View full text |Cite
|
Sign up to set email alerts
|

An eye movement based reading intervention in lexical and segmental readers with acquired dyslexia

Abstract: Due to their brain damage, aphasic patients with acquired dyslexia often rely to a greater extent on lexical or segmental reading procedures. Thus, therapy intervention is mostly targeted on the more impaired reading strategy. In the present work we introduce a novel therapy approach based on real-time measurement of patients' eye movements as they attempt to read words. More specifically, an eye movement contingent technique of stepwise letter de-masking was used to support sequential reading, whereas fixatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 65 publications
0
6
0
Order By: Relevance
“…Thus, the assumption here was that prolonged gaze durations and higher fixation counts for words are taken to reflect sublexical decoding-based processes. In contrast, single fixations and shorter gaze durations, expected for the easiest items (i.e., familiar visual words), are suggestive of lexical reading via direct orthographic whole-word recognition (Hawelka et al., 2010; Schattka et al., 2010; Ablinger et al., 2014). For the present study, the selected PW received a significantly higher number of fixations and longer gaze durations ( M ± SD = 3.26 ± 1.02 and 877 ms ± 253) than the selected LFW ( M ± SD = 2.48 ± 0.52 and 610 ms ± 130) and those with HFW ( M ± SD = 1.79 ± 0.31 and 422 ms ± 66), with stimulus length controlled; all differences between conditions were highly significant ( p < 0.001).…”
Section: Methodsmentioning
confidence: 94%
“…Thus, the assumption here was that prolonged gaze durations and higher fixation counts for words are taken to reflect sublexical decoding-based processes. In contrast, single fixations and shorter gaze durations, expected for the easiest items (i.e., familiar visual words), are suggestive of lexical reading via direct orthographic whole-word recognition (Hawelka et al., 2010; Schattka et al., 2010; Ablinger et al., 2014). For the present study, the selected PW received a significantly higher number of fixations and longer gaze durations ( M ± SD = 3.26 ± 1.02 and 877 ms ± 253) than the selected LFW ( M ± SD = 2.48 ± 0.52 and 610 ms ± 130) and those with HFW ( M ± SD = 1.79 ± 0.31 and 422 ms ± 66), with stimulus length controlled; all differences between conditions were highly significant ( p < 0.001).…”
Section: Methodsmentioning
confidence: 94%
“…The analyses of eye movements have recently also been applied to the diagnosis and treatment of reading impairment after brain damage, such as acquired central dyslexia (Ablinger, von Heyden, et al, 2014;Kim & Lemke, 2016;Schattka, Radach, & Huber, 2010) 1 . There is also an emerging interest in using eye tracking to examine silent reading and sentence/text comprehension in aphasia (Chesneau, Joanette, & Ska, 2007;Kim & Bolger, 2012;Knilans & DeDe, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…For persons with neurological damage, the interaction between oculomotor and cognitive systems can be impaired, resulting in eye movements that are reflective of the underlying damage. Little work to date has characterized the oculomotor function of individuals with aphasia (but see Ablinger et al, 2014a,b; Kim and Lemke, 2016), a language disorder that is often caused by brain damage due to a stroke. The current study sought to investigate oculomotor control in individuals with aphasia over a range of circumstances.…”
Section: Introductionmentioning
confidence: 99%
“…There is a growing body of work that uses eye tracking to investigate language processing (Dickey et al, 2007; Yee et al, 2008; Thompson and Choy, 2009; Cho and Thompson, 2010; Schattka et al, 2010; Mirman et al, 2011; Meyer et al, 2012; Mack et al, 2013; Hanne et al, 2015; Kim and Lemke, 2016), attention (Heuer and Hallowell, 2015), working memory (Ivanova and Hallowell, 2012), and reading (e.g., Ablinger et al, 2014a) in PWA. Some of these studies have demonstrated the feasibility and validity of using eye movements to measure linguistic (e.g., Ablinger et al, 2014b) and non-linguistic cognitive processing (Ivanova and Hallowell, 2012; Heuer and Hallowell, 2015), as well as outcomes related to treatment (e.g., Kim and Lemke, 2016). Other studies have examined specific aspects of sentence processing in individuals with aphasia (e.g., Mack et al, 2013; Hanne et al, 2015), or distinct processing patterns in both behavioral and eye movement data between PWA and control participants (e.g., Dickey et al, 2007).…”
Section: Introductionmentioning
confidence: 99%